IFRS for Dummies - Steven Collings (England John Wiley & Sons, Ltd, 2012)
The easy way to get a grip on International Reporting Standards IFRS For Dummies is your complete introduction to IFRS and international accounting and balancing standards. Combining all the facts needed to understand this complex subject with useful examples, this easy-to-read guide will have you on top of IFRS in no time. In plain English, it helps you make sense of IFRS and your understanding of: what they are and where they apply; how to adopt IFRS for the first time; how IFRS affects the key components of your financial statements; how to disclose information in financial statements; and much more. Covers what to do if you're applying IFRS for the first time Explains complicated material in plain English Helps you make sense of this principles-based set of standards that establish broad rules for financial reporting If you're an accountant, student, or trainee in need of accessible information on IFRS, this hands-on, friendly guide has you covered.
Keywords: (ASB-2515) Financial Accounting; (ASB-2516) Financial Accounting